BÚZIOS: TODA TEMPORADA! A RELAÇÃO EDUCAÇÃO, TURISMO E CULTURA: ESTUDO DE CASO DO TECTUR/CEJOB - Oliveira, Sandra Regina dos Anjos (2006)
The objective of this study is to find out whether the valorization of culture is present on the discourse of the students of the Technical Course in Tourism of the João de Oliveira Botas State School-Tectur, located at Armação de Búzios, Rio de Janeiro, Brazil. Based on the explanatory study, this work analyses the theme with the case study method, and the main instruments were semi-structured interviews, and bibliographic and documental research. Books, articles and documents available in local offices as well as filed records were consulted, and in loco direct observations were carried on. The study presents the situation problem and a succinct scenario of the town, and then discusses the literature regarding technical professional courses, tourism and hospitality, and the importance of valorizing the cultural diversity to Education and Tourism, according to the UNESCO, the National Tourism Plan and the Tourism Director Plan of the State of Rio de Janeiro. The analysis of the interviews with the Tectur s students and professionals lead to the conclusion that the valorization of culture, although present in the students discourse, is still disorganized and often associated to short economic incomes, what is justified by the lack of a real recognition of what is or is not a local cultural expression, derived from the Búzios roots. Finally, the study discusses the data and gives suggestions to solve the problem.